2018
DOI: 10.4103/1673-5374.238714
|View full text |Cite
|
Sign up to set email alerts
|

Kaempferol attenuates cognitive deficit via regulating oxidative stress and neuroinflammation in an ovariectomized rat model of sporadic dementia

Abstract: Alzheimer's disease (AD) is associated with oxidative stress, and ultimately results in cognitive deficit. Despite existing literature on the pathophysiology of AD, there is currently no cure for AD. The present study investigated the effects of kaempferol (Kmp) isolated from the extract of Mespilus germanica L. (medlar) leaves on cognitive impairment, hippocampal antioxidants, apoptosis, lipid peroxidation and neuro-inflammation markers in ovariectomized (OVX) rat models of sporadic AD. Kaempferol, as the mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(55 citation statements)
references
References 34 publications
1
39
0
Order By: Relevance
“…Meanwhile, phytochemical analysis of the KBD extract by HPLC fingerprint method revealed the presence of piperine (1), madecassoside (2), asiaticoside (3), quercetin (4), kaempferol (5), kaempferol-3-glucoside (6), rutin 7, luteolin-7-O-glucoside (8), and ferulic acid (9). The radical scavenging and antioxidant activities of these compounds have been extensively reported [35][36][37][38]. Moreover, accumulating evidences suggested that these dietary phytochemicals potently strengthen the antioxidative potential through the modulation of the Nrf2/antioxidant responsive element (ARE) signaling pathway [39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, phytochemical analysis of the KBD extract by HPLC fingerprint method revealed the presence of piperine (1), madecassoside (2), asiaticoside (3), quercetin (4), kaempferol (5), kaempferol-3-glucoside (6), rutin 7, luteolin-7-O-glucoside (8), and ferulic acid (9). The radical scavenging and antioxidant activities of these compounds have been extensively reported [35][36][37][38]. Moreover, accumulating evidences suggested that these dietary phytochemicals potently strengthen the antioxidative potential through the modulation of the Nrf2/antioxidant responsive element (ARE) signaling pathway [39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…It enhances cognition and memory by uplifting antioxidant defense system, cholinergic signaling, and synaptic plasticity (Ishola et al, 2019). Kaempferol attenuates cognitive deficit through regulating antioxidants and neuro-inflammation (Kouhestani et al, 2018), promotes memory retention and density of hippocampal CA1 neurons (Darbandi et al, 2016). The flavonoid, quercetin has potential therapeutic benefit in AD.…”
Section: Pathological Aspects and Drug Targetsmentioning
confidence: 99%
“…It is reported to be particularly effective against ailments involving inflammation [ 27 ], cancer [ 28 ], and oxidative stress [ 29 ] through modulation of molecular pathways such as NF-kB, PI3k/AKT, MAPK, Bcl2, Caspase 3, and VEGF [ 30 ]. It is of note that kaempferol is capable of exerting beneficial effects against central nervous system disorders as well, such as depression [ 31 ], anxiety [ 32 ], and cognitive deficit [ 33 ]. Keeping in view the aforementioned reports, the present study was designed to observe the effect of kaempferol on fear memory processing and associated anxiety in the context of eCB modulation.…”
Section: Introductionmentioning
confidence: 99%